The Moral Status Of Animal in the Religious Philosophy of Saint Augustine and Thomas Aquinas: A Critical Study based on Humanistic Ethos - Sivakaran, N. (University of jaffna, 2018)
The overall purpose of this is to analyze, critically, the moral status of animal based on the arguments of saint Augustine and Thomas Aquinas. Moral status is a characteristic which could be applied to and entity, such as a person or animal. This objective was analyzed by tackling three central research questions. (a) How are we to understand the moral status of animals? (b) Are human being superior to other living organisms in the ecosystems? (c) Are rights only confined to human being? The moral status of animals in human society has been long debated in the literature of animal ethics. Philosophers and Theologians have taken several positions to determine the factors of moral status. There were variety of the factors discussed in the ethical literature. This study, however, mainly focused on following factors which were reason-rational thinking, language - communication, rights and duty, pain and pleasure, values – inherent value and intrinsic value. Two types of arguments were analysed in this study. One side of the argument was that moral status should be confined to humans only. This types of argument is called anthropocentrism. Augustine and Thomas Aquinas come under the anthropocentrism. The other type of argument was that moral status should be extended to nonhuman living organisms in the ecosystems as well. This type of argument is called ecocenterism. This study also aims to analyze the justifications given by the both side of arguments in order to discover whether any of those justifications are valid reasons. The data were gathered to find valid answer to questions through the analysis of arguments made by various philosophers, religious scriptures, ethical norms and principles and moral responsibility of human for respect and care. Inductive and deductive methods as well as content analysis also were used in order to strengthen rational moral arguments. The discussion part, anthropocentrism and ecocentrism were critically discussed. Deontology and virtue ethics and utilitarianism were used as a tool to debate in the relation of human and non non human. In concluding part, the paper provides some ethical recommendation for necessity of prevention of animals and ecosystem for future generation.
Keywords: Moral status; Animal; Augustine and thomas aquinas; Anthropocentrism; Ecocenterism